Digital transformation and moving towards developing smart libraries: Transforming library as educational/ institution repositories - Edited by Keshava...at.el. (New Delhi D. P. S. Publishing, 2022)
About digital transformation and developing the library.
Keywords: Digital Library; Smart Libraries